# Confused with a limit problem. [closed]

$$\lim_{n \to \infty} \frac{\big((n+1)(n+1)(n+3)......3n\big)^{1/n}}{(n^{2n})^{1/n}}= ?$$

## closed as off-topic by user21820, user91500, Watson, Laurent Duval, user99914 Jun 12 '16 at 10:18

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – user21820, user91500, Watson, Laurent Duval, Community
If this question can be reworded to fit the rules in the help center, please edit the question.

• So, essentially, $\lim_{n \to \infty} \left[ \frac{(3n)!}{n!(n^{2n})} \right]^{1/n}$? Have you considered using Stirling? (I haven't looked at this closely, but I would guess it would answer this...) – Brian Tung Jun 12 '16 at 5:54
• Show you working, why are you stuck? – Abhijit A J Jun 12 '16 at 5:55
• i need the answer in the form e^x. What's Stirling? @BrianTung – Tejesh Atr Jun 12 '16 at 5:57
• Here's the Wikipedia article on it. – Brian Tung Jun 12 '16 at 5:58
• thanks. But what's the answer to the above question? – Tejesh Atr Jun 12 '16 at 6:02

You want to compute $\lim_{n\rightarrow \infty} ((n+1)(n+2)\cdots(3n))^{1/n} /n^2 = \lim_{n\rightarrow \infty} ((3n)!/n!)^{1/n}/n^2$

By Stirling's approximation, this becomes $\lim_{n \rightarrow \infty} (\sqrt{6 \pi n} (3n/e)^{3n} / (\sqrt{2 \pi n} (n/e)^n))^{1/n} / n^2$ which can be simplified to $\lim_{n \rightarrow \infty} (27^n\sqrt{3} (n/e)^{2n})^{1/n} / n^2 = \lim_{n \rightarrow \infty} 27\cdot3^{1/2n}\cdot (n/e)^{2} / n^2 = 27/e^2$.

And here's some numerical verification https://ideone.com/hwHyVI

• I am unaware of Stirling's approximation. Is there any simpler method? Thanks. – Tejesh Atr Jun 12 '16 at 6:16

(No Stirling's approx.)

Result: If $\lim_{n \to \infty }\frac{a_{n+1}}{a_n}=l$ then $\lim_{n\to\infty} (a_n)^{1/n}=l.$

So all we need to find is just limit of $\frac{a_{n+1}}{a_n}.$

Now given $a_n=\frac{(3n)!}{n!n^{2n}}$ so $a_{n+1}=\frac{(3(n+1))!}{(n +1)!(n+1)^{2(n+1)}}$. So $$\lim_{n\to \infty}\frac{a_{n+1}}{a_n}=\lim_{n\to \infty}\frac{(3(n+1))! n!n^{2n}}{(n+1)!(n+1)^{2(n+1)}(3n)!}\\=\lim_{n\to \infty}\frac{3(n+1)(3n+2)(3n+1)n^{2n}}{(n+1)^3(n+1)^{2n}}\\=\lim_{n\to \infty}\frac{3(3n+2)(3n+1)}{(n+1)^2}\left(\frac{n}{n+1}\right)^{2n}\\=\lim_{n\to \infty}\frac{3(3+\frac{2}{n})(3+\frac{1}{n})}{(1+\frac{1}{n})^2}\left(\frac{n}{n+1}\right)^{2n}=\frac{27}{e^2}$$

May be you don't need any approximation for this question. You can do it directly.

First, take ln both the sides and arrange it in this way $$lnL=\lim_{n\to\infty}(\sum_{i=1}^{2n}\frac{\ln(i+n)}{n}-\sum_{i=1}^{2n}\frac{\ln(n)}{n})$$ I have arranged the second term in form of a summation. Now combine both of the summations $$\sum_{i=1}^{2n}\frac{\ln(\frac{i}{n}+1)}{n}$$. Now assume $\frac{i}{n}$ as $t$ and $\frac{1}{n}$ as $dt$ . So now this limits is converted to a integration $$lnL=\int_{t=0}^2 ln(1+t)dt$$ Limits are decided by $t=\lim_{n\to\infty}(\frac{i}{n})$ . Put the values of $i=1$ to $i=2n$, you will get the limits. So now integration is $lnL=\int_{t=1}^3 ln(t)dt=3ln3-2$ which means $$L=\frac{27}{e^2}$$ Final answer without any approximation.

In the same spirit as other answers and comments, let us consider $$A_n= \left[ \frac{(3n)!}{n!(n^{2n})} \right]^{1/n}$$ Taking logarithms $$\log(A_n)=\frac 1 n\left(\log(3n!)-\log(n!)-2n\log(n) \right)$$ Now, using Stirling approximation $$\log(k!)\sim k\log\left(\frac k e\right)+\frac 12 \left(\log(k)+\log(2\pi)\right)$$ Replacing, expanding the logarithms and simplifying leads to $$\log(A_n)\sim \frac 1 n\left( n (\log (27)-2)+\frac{\log (3)}{2}\right)=\log (27)-2+\frac{\log (3)}{2 n}=\log\left(\frac{27}{e^2}\right)+\frac{\log (3)}{2 n}$$ which shows the limit and how it is approached.